Benefit of tolvaptan in the management of hyponatraemia in patients with diuretic‐refractory congestive heart failure: the SEMI‐SEC project. (19th January 2017) - Pose, Antonio; Almenar, Luis; Gavira, Juan José; López‐Granados, Amador; Blasco, Teresa; Delgado, Juan; Aramburu, Oscar; Rodríguez, Avelino; Manzano, Luis; Manito, Nicolás
Abstract: Aims: Hyponatraemia is an electrolyte disorder that occurs in advanced congestive heart failure (HF) and worsens prognosis. We explored the usefulness of tolvaptan, which has shown promising results in the treatment of this condition. Methods and results: This study is based on a retrospective national registry (2011–15) of patients hospitalized with refractory HF and hyponatraemia who agreed to receive tolvaptan when standard treatment was ineffective. The benefit of tolvaptan was analysed according to the following criteria: normalization ([Na + ] ≥ 135 mmol/L) or increased sodium levels [Na + ] ≥ 4 mEq/L on completion of treatment, and increase in urine output by 300 or 500 mL at 48 h. Factors associated with tolvaptan benefit were explored. A total of 241 patients were included, 53.9% of whom had ejection fraction <40%. All patients received concomitant loop diuretics. Initial tolvaptan dose was 17.2 ± 6.1 mg, and end dose was 26.4 ± 23.2 mg (duration 7.8 ± 8.6 days). Serum sodium concentrations increased significantly at 24–48 h, from 126.5 ± 6.2 mEq/L at baseline to 134.1 ± 6.1 mEq/L at the end of treatment ( P  < 0.0001). Weight fell by ~5 kg before discharge ( P  < 0.0001) and urine output increased 1.3‐fold ( P  < 0.0001). Normal sodium levels and/or increases of 500 mL in urine output were achieved by 90.8% of patients (35.7% achieved both) and 94.8% increased to [Na + ] ≥ 4 mEq/L and/or +300 mL in urine output (54.4% both). Conclusions: An increase in sodium levels and/or improvement in urine output was observed in patients admitted for HF and refractory hyponatraemia under tolvaptan treatment. Tolvaptan may be useful in this setting, in which no effective proven alternatives are available.